Recent trends in the development of reactor systems for hydrogen production via methanol steam reforming. (19th January 2022) - Kang, Jeongmee; Song, Youjung; Kim, Taejun; Kim, Sungtak
Abstract: Hydrogen is currently receiving significant attention as an alternative energy resource, and among the various methods for producing hydrogen, methanol steam reforming (MSR) has attracted great attention because of its economy and practicality. Because the MSR reaction is inherently activated over catalytic materials, studies have focused on the development of noble metal-based catalysts and the improvement of existing catalysts with respect to performance and stability. However, less attention has been paid to the modification and development of innovative MSR reactors to improve their performance and efficiency. Therefore, in this review paper, we summarize the trends in the development of MSR reactor systems, including microreactors and membrane reactors, as well as the various structured catalyst materials appropriate for application in complex reactors. In addition, other engineering approaches to achieve highly efficient MSR reactors for the production of hydrogen are discussed. Graphical abstract: Image 1 Highlights: Development trends and technologies for representative techniques used in hydrogen purification are presented. Catalytic purification via hydrogen-oxygen recombination reactions is focused on here. Pd or Pt-based catalysts should require further development to overcome deactivation during the reaction.